Simulação numérica tridimensional de uma bomba MHD de corrente alternada - Campos, Matheus de Abreu Monteiro (2020)
In this work, the numerical simulation of a three-dimensional magnetohydrodynamic (MHD) pump of alternating current is made. The goal of this work is to evaluate the implications caused by the alternating current over the fluid flow and compare them with a direct current case, in which the average Lorentz force exerted by the pump is equivalent. A model for the problem is presented and computationally implemented. The computational model is validated using experimental data available in the literature. During the validation step some turbulence models are evaluated and the most suitable for the alternating current problem is selected. A group of dimensionless numbers is raised in order to improve the problem analysis and justify some simplifications done in the model. At last, a range of frequency from 1 Hz to 50 Hz is simulated. Results show that around 10 Hz there is a high concordance between velocity profiles for DC and AC equivalent cases, while for other frequencies some periodicity is observed. Heating produced by Joule effect is higher for the AC pump and may be critic for its operation. Other quantities as current density and pressure are also evaluated.